Africa RISING West Africa 2014-2016 work plan - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2014)
The Africa RISING West Africa project (AR‐WA) is being implemented by multi‐disciplinary research teams and development partners from the public and private sectors in collaboration with farmers and communitybased organizations (CBOs) at intervention communities in northern Ghana and southern Mali. The work plan presented here consists of 10 work‐packages (WP), covering Research Output 1 (Situation Analysis – WP‐1) and Research Output 2 (Integrated Systems Improvement – WP‐2 to 10) of the Africa RISING Framework. It does not cover research on Scaling‐up and Delivery Systems (Research Output 3) per se, but various delivery approaches will be used to exchange knowledge and disseminate technologies in WP 2‐10. The work‐packages are: WP‐1: Socio‐economic studies on sustainable intensification in northern Ghana and southern Mali; WP‐2: Raising and sustaining productivity in cereal‐legume cropping systems in northern Ghana; WP‐3: Biological control of aflatoxins in maize with Aflasafe Ghanaian product GH01; WP‐4: Integrating vegetables into cereallegume cropping systems in northern Ghana; WP‐5: Improving farm and field productivity and profitability in northern Ghana; WP‐6: Intensifying livestock and poultry production in northern Ghana and southern Mali; WP‐7: Raising and sustaining productivity in crop‐livestock systems in northern Ghana; WP‐8: Land, soil and water management to intensify cereal‐legume farming systems in Ghana; WP‐9: Managing natural resources to increase watershed productivity in southern Mali; and WP‐10: Improving household nutrition and value addition in northern Ghana and southern Mali. Planned activity for the research output on scaling and delivery will focus on comparison of delivery approaches used in both countries. A series of cross‐cutting activities are planned. Key amongst them is: building the capacity of young female and male scientists for data management and analysis and integrated crop‐livestock production.